Multifunctional Conjugated Ligand Engineering for Stable and Efficient Perovskite Solar Cells. Issue 32 (5th July 2021) - Ma, Ke; Atapattu, Harindi R.; Zhao, Qiuchen; Gao, Yao; Finkenauer, Blake P.; Wang, Kang; Chen, Ke; Park, So Min; Coffey, Aidan H.; Zhu, Chenhui; Huang, Libai; Graham, Kenneth R.; et al.
Abstract: Surface passivation is an effective way to boost the efficiency and stability of perovskite solar cells (PSCs). However, a key challenge faced by most of the passivation strategies is reducing the interface charge recombination without imposing energy barriers to charge extraction. Here, a novel multifunctional semiconducting organic ammonium cationic interface modifier inserted between the light‐harvesting perovskite film and the hole‐transporting layer is reported. It is shown that the conjugated cations can directly extract holes from perovskite efficiently, and simultaneously reduce interface non‐radiative recombination. Together with improved energy level alignment and the stabilized interface in the device, a triple‐cation mixed‐halide medium‐bandgap PSC with an excellent power conversion efficiency of 22.06% (improved from 19.94%) and suppressed ion migration and halide phase segregation, which lead to a long‐term operational stability, is demonstrated. This strategy provides a new practical method of interface engineering in PSCs toward improved efficiency and stability. Abstract : One of the challenges in perovskite solar cells is passivating the perovskite surface without hindering charge extraction. In this work, a conjugated ligand is introduced to the interface between perovskite and hole‐transporting layer, showing efficient hole extraction with improved energy level alignment and suppressed phase segregation. Therefore, devices with high efficiency and stability are achieved.